2015
DOI: 10.1136/acupmed-2014-010720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupressure on Anxiety: A Systematic Review and Meta-Analysis

Abstract: Acupressure seems to be effective in providing immediate relief of pretreatment anxiety among adults, and has a medium effect size. However, conflicting results were found for the improvements on physiological indicators. More rigorous reporting, including allocation concealment procedure, is needed to strengthen the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 21 publications
(63 reference statements)
5
49
0
1
Order By: Relevance
“…In addition, our study focused on community-dwelling participants, not hospitalized patients, and revealed the effectiveness of aroma massages in reducing anxiety among this population. Furthermore, Au et al found that anxiety following surgery was relieved by acupressure in 5 RCT studies [37], and this may help explain the reduction of state anxiety scores after aroma foot massage in this study. In other words, the reduction found in this study might be partially contributable to stimulation of acupuncture points as well as aroma foot massage.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, our study focused on community-dwelling participants, not hospitalized patients, and revealed the effectiveness of aroma massages in reducing anxiety among this population. Furthermore, Au et al found that anxiety following surgery was relieved by acupressure in 5 RCT studies [37], and this may help explain the reduction of state anxiety scores after aroma foot massage in this study. In other words, the reduction found in this study might be partially contributable to stimulation of acupuncture points as well as aroma foot massage.…”
Section: Discussionsupporting
confidence: 53%
“…Median APAISa level in the acupuncture group, but not in the control group: 10 (6-13 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]) to 7 (4-10 [4-18]), p < 0.001 vs. 9 (6-13 [4-18]) to 8.5 (6-12 [4-18]), p = 0.872, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis on the use of acupressure for the management of anxiety concluded that acupressure was an effective anxiolytic, with a 'medium' treatment effect size observed [10]. This review included five randomised controlled trials (n = 314), but two of the studies examined anxiety in patients during transport, as opposed to before surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also some evidence that acupressure may improve depression [19], anxiety [26] and QoL [21]. However, some studies have methodological limitations as well as variation in acupressure techniques and the selection of acupoints [19,20,26]. Future well-designed studies, using standardised treatment protocols, are required to provide evidence of acupressure's usefulness in clinical practice.…”
Section: Introductionmentioning
confidence: 99%